Digi Board 2: Type 3910 - Technical Description - Hps SystemTechnik
The Digi Board 2 has been developed for basic and further training in the fundamentals of digital technology, non-contact control engineering and microcomputer technology. All the fuction groups required to conduct the experiments in degital technology are built into the DIGI BOARD 2 and are powered by an interated power supply unit. The indibidual function groups are conected in 2mm conecting technology. AII IC components are inserted in sockets. The DIGI BOARD 2 can also used as mobile training unit simply by screwing it into a BOX